JURNAL ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN PPK-BLUD PADA RSUD KARDINAH - Debby Firoeza Indiany; Dien Noviany Rahmatika; Jaka Waskito (Multiplier: Jurnal Magister Manajemen, 2016)
RSUD Kardinah Kota Tegal in December, 2008 has been designated as Badan Layanan Umum Daerah (BLUD), then since January 2009 has done changes management finances, with the financial management apply system that is called â€œPola Pengelolaan Keuangan Badan Layanan Umum Daerahâ€ (PPK â€“ BLUD). This study aimed to analyze the diffrerences in financial performance RSUD Kardinah based on (1) the ratio of the vulnerability, the aspects of return of assets, return on equity, gross profit margin and net profit margin. (2) liquidity ratios include aspects of current ratio, quick ratio and cash ratio (3) solvency ratios include aspects of debt ratios, debt to equity ratio and times interest earned ratio, and (4) the ratio of activity includes aspects of accounts receivable turn over, inventory turn over, fixed assets and total assets turn over before and after implementing PPK-BLUD. This study classified quantative descriptive research the type of data used is secondary data obtained from the annual financial statements of RSUD Kardinah, the period before implementing ppk â€“ blud (2002 â€“ 2008) and after implementing ppk â€“ blud (2009 â€“ 2015). The analytical method used is a diferrent test to test the hypothesis using wilcoxon test with an error rate (alpha) of 5%. The result of this study conclude, there are no significant differences in financial performance based suspectible ratio, liquidity ratio and activity ratio on RSUD Kardinah before and after implementing of PPK-BLUD. There are significant differences in the aspect ratio of the activity inventory turn over snd fixed assets turn over before and after implementing of PPK â€“ BLUD. The implementation of the PPK â€“ BLUD in hospitals Kardinah not give any significant changes to be seen from the ratio financial ratio, but there is an increase in the trend sharp against the income operations hospital after the implementation of PPK â€“ BLUD. Keywords : PPK-BLU, financial ratio analysis, financial performance, Wilcoxon Siged Ranks Test